Updated carrier rates for c.35delG (GJB2) associated with hearing loss in Russia and common c.35delG haplotypes in Siberia - Marina V. Zytsar; Nikolay A. Barashkov; Marita S. Bady-Khoo; Olga A. Shubina-Olejnik; Nina G. Danilenko; Alexander A. Bondar; Igor V. Morozov; Aisen V. Solovyev; Valeriia Yu. Danilchenko; Vladimir N. Maximov; Olga L. Posukh (BMC, 2018)
Abstract Background Mutations in GJB2 gene are a major causes of deafness and their spectrum and prevalence are specific for various populations. The well-known mutation c.35delG is more frequent in populations of Caucasian origin. Data on the c.35delG prevalence in Russia are mainly restricted to the European part of this country. We aimed to estimate the carrier frequency of c.35delG in Western Siberia and thereby update current data on the c.35delG prevalence in Russia. According to a generally accepted hypothesis, c.35delG originated from a common ancestor in the Middle East or the Mediterranean ~ 10,000-14,000 years ago and spread throughout Europe with Neolithic migrations. To test the c.35delG common origin hypothesis, we have reconstructed haplotypes bearing c.35delG and evaluated the approximate age of c.35delG in Siberia. Methods The carrier frequency of c.35delG was estimated in 122 unrelated hearing individuals living in Western Siberia. For reconstruction of haplotypes bearing c.35delG, polymorphic D13S141, D13S175, D13S1853 flanking the GJB2 gene, and intragenic rs3751385 were genotyped in deaf patients homozygous for c.35delG (n = 24) and in unrelated healthy individuals negative for c.35delG (n = 67) living in Siberia. Results We present updated carrier rates for c.35delG in Russia complemented by new data on c.35delG carrier frequency in Russians living in Western Siberia (4.1%). Two common D13S141-c.35delG-D13S175-D13S1853 haplotypes, 126-c.35delG-105-202 and 124-c.35delG-105-202, were reconstructed in the c.35delG homozygotes from Siberia. Moreover, identical allelic composition of the two most frequent c.35delG haplotypes restricted by D13S141 and D13S175 was established in geographically remote regions: Siberia and Volga-Ural region (Russia) and Belarus (Eastern Europe). Conclusions Distribution of the c.35delG carrier frequency in Russia is characterized by pronounced ethno-geographic specificity with a downward trend from west to east. Comparative analysis of the c.35delG haplotypes supports a common origin of c.35delG in some regions of Russia (Volga-Ural region and Siberia) and in Eastern Europe (Belarus). A rough estimation of the c.35delG age in Siberia (about 4800 to 8100 years ago) probably reflects the early formation stages of the modern European population (including the European part of the contemporary territory of Russia) since the settlement of Siberia by Russians started only at the end of sixteenth century.